Silver trifluoromethanesulfonate and metallic copper mediated syntheses of 1, 2, 3-triazole-O- and triazolyl glycoconjugates: consecutive glycosylation and cyclization under one-pot condition. Issue 29 (20th July 2016) - Dutta, Samrat; Gupta, Shyam Ji; Sen, Asish Kumar
Graphical abstract: Highlights: Syntheses of 1, 2, 3-triazole- O - and triazolyl glycoconjugates using AgOTf and Cu(0). One-pot process for consecutive glycosylation and azide alkyne cyclization. The process is rapid and does not require isolation of intermediates. AgOTf acts as promoter for glycosylation and co-catalyst for cyclization reaction. Several 1, 2, 3-triazole- O - and triazolyl glycoconjugates have been synthesized. Abstract: A new protocol for synthesis of 1, 2, 3-triazole glycoconjugates has been described. The reaction involves consecutive glycosylation and azide alkyne cyclization under one-pot condition using a combination of AgOTf and Cu(0) catalyst. Here, AgOTf acts as a promoter for the glycosylation reaction and then as a co-catalyst for the subsequent click reaction.